A new species of Dactylopius Costa (Dactylopius gracilipilus sp. nov.) (Hemiptera: Coccoidea: Dactylopiidae) from the Chihuahuan Desert, Texas, U.S.A. - van Dam, Alex R.; May, Bernie (Zootaxa, 2012)
A new species of Dactylopius Costa (Dactylopius gracilipilus Van Dam & May) is described and illustrated. It is morpho-logically similar to Dactylopius tomentosus (Lamarck), but has more gracile truncate setae, abundant simple pores dorsally, and appears to be host-restricted to Corynopuntia Knuth (Cactaceae: Opuntioidea).